On the Book of Viсtor Kagan "Autism in Children", 2nd Edition, Supplemented - N. Iovchuk; A. Severniy (Moscow State University of Psychology and Education, 2019)
First published in 1981 and actual until nowadays, the book of Victor Kagan "Autism in Children" reprinted at "Smysl" Publishing House. Based on the vast literature, presented edition of the book describes the history of the development of the problem of autism since the beginning of the 20th century. Author formulates owns' definition of autism, describes the clinical picture of childhood autism, as well as autism as a psychopathological nonspecific syndrome in the schizophrenia, schizoid psychopathy and paraautistic reactions. The author dwells in detail on the identification of differential diagnostic criteria, treatment and psychotherapy of autism. The book includes a chapter on the epidemiology of childhood autism, the reasons for the dramatic increase in autism indicators, among which the first place is not clinical criteria, but socio-financial benefits. Fundamental papers of L. Kanner and G. Asperger are at the end of the monograph.